Anf Effort for Improving 3B Students’ Learning Result of Tarikh Islam Subject Using Mind Mapping Method in Gontor for Girls - Dwi Jayanti; Defi Firmansah (Educan : Jurnal Pendidikan Islam, 2018)
Some  factors that affect learning process it is able to give positive support for the learning itself, but it also able to inhibit the learning process. The obstacles may affect people’s learning result and then they experience the learning process that not appropriate with what they want. These conditions impact to problem appaearance in the next learning process. Low students learning motivation will be an important obstacle in the learning process, because it can caused low students learning achievement. Thus, teachers are expected to improve students learning motivation to improve students learning achievement. This research is Classroom Action Research  (CAR) which aim to give information about how the proper action to improve students learning reslt for Tarikh Islam subject in the learning process through mind mapping method. The result of this research showed that learning method and learning media that used by the teachers are very important to improve students’ understanding and it impact to students learning improvement in the certain subject. It can be seen from the research result that was done to the students grade 3B in Pondok Modern Darussalam Gontor for Tarikh Islam subject, the use of mind mapping method for this subject improve students learning result 28%.